2020
DOI: 10.1007/s12038-020-00111-9
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis approach for comprehensive screening of salt stress-tolerant tomato germplasm at the seedling stage

Abstract: Salt stress is a major abiotic factor that affects the growth and yield of crops. The present study was carried out to assess the salt tolerance among the Arka Samrat, Arka Rakshak, YVU-1, S-22, YVU-2, and PKM-OP tomato germplasms using principal component analysis (PCA). Different salt (NaCl) concentrations like control, 0.04 M, 0.12 M, and 0.20 M were selected in order to classify them into sensitive and tolerant tomato germplasms based on 13 parameters. A significant variation was observed among the selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…It is well known that salt stress severely impacts crop production worldwide by reducing growth and yield [14,15]. Specifically, the growth parameters of different germplasms show significantly different responses to salt stress, such as the germplasms of cucumber, tomato, and chilli [6][7][8]. In asparagus, we also found that 95 germplasm accessions exhibited different salt tolerance with a large variation.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…It is well known that salt stress severely impacts crop production worldwide by reducing growth and yield [14,15]. Specifically, the growth parameters of different germplasms show significantly different responses to salt stress, such as the germplasms of cucumber, tomato, and chilli [6][7][8]. In asparagus, we also found that 95 germplasm accessions exhibited different salt tolerance with a large variation.…”
Section: Discussionmentioning
confidence: 55%
“…In recent years, considerable research on the identification of salt-tolerant germplasm has been carried out in multiple vegetables around the world, such as cucumber, tomato, and chilli [6][7][8], from which some success and experience have been achieved. However, in asparagus, the research is still in the initial stage and lacks depth and breadth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a range of crops, salinity tolerance at early growth stages often reflects greater tolerance than at later growth stages. For different crops, including tomatoes [ 28 , 29 , 38 ], barley [ 39 ], wheat [ 40 ], maize [ 41 ], cotton [ 42 ], and rice [ 43 ], research has shown that genotypes with enhanced tolerance mechanisms have been selected for their resilience to saline environments at the seedling stage. The aim of our present study was to identify salinity tolerance by phenotyping tomato seedlings using quantitative traits such as reduction in mass of roots and shoots, leaf injury due to salt stress, and tolerance indices derived from dry weights and leaf inorganic ions (K + , Na + , and Ca 2+ ) in order to systematically screen salt-tolerant varieties as well as to understand the biochemical mechanisms of salinity stress tolerance in tomatoes.…”
Section: Discussionmentioning
confidence: 99%
“…Simple correlation analysis is preferred, with pairwise regression of attributes, but it may not give expected results with complex salinity traits. Hence, the use of principal component analysis (PCA) can illustrate the most significant plant attributes governing salt tolerance [ 28 ]. In PCA, a three-way interaction plot aided with clustering can provide efficient prediction of the responses of salinity stress tolerance of the cultivars relying on trait associations existing between morpho-physiological traits and Na + stress [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%